Outdoor light at night, overweight, and obesity in school-aged children and adolescents. (15th July 2022) - Lin, Li-Zi; Zeng, Xiao-Wen; Deb, Badhan; Tabet, Maya; Xu, Shu-Li; Wu, Qi-Zhen; Zhou, Yang; Ma, Hui-Min; Chen, Duo-Hong; Chen, Gong-Bo; Yu, Hong-Yao; Yang, Bo-Yi; et al.
Abstract: Previous studies have indicated that outdoor light at night (LAN) is associated with a higher prevalence of overweight or obesity in adults. However, the association of LAN levels with overweight or obesity in children is still unknown. This study utilized data from the Seven Northeastern Cities study, which included 47, 990 school-aged children and adolescents (ages 6–18 years). Outdoor LAN levels were measured using satellite imaging data. Weight and height were used to calculate age-sex-specific body mass index (BMI) Z-scores based on the World Health Organization (WHO) growth standards. Overweight status and obesity were defined using the Chinese standard. Information regarding socioeconomic status, sleep-related characteristics, and obesogenic factors were obtained using a questionnaire. A generalized linear mixed model examined the associations of outdoor LAN levels (in quartiles) with the outcomes of interest. Compared to children in the lowest quartile of outdoor LAN levels, children exposed to higher outdoor LAN levels had larger BMI Z-scores and higher odds of being overweight (including obesity) or obese, with the largest estimates in the third quartile [BMI Z-score: β = 0.26, 95% CI: 0.18–0.33; overweight (including obesity): OR = 1.40, 95% CI: 1.25–1.56; obesity: OR = 1.46, 95% CI: 1.29–1.65]. There was a significant sex difference ( P interaction <0.001) in the association of outdoor LAN levels with BMI Z-scores, and the association was stronger in males. Results remained robust following multiple sensitivity analyses and the adjustment of sleep-related characteristics, obesogenic factors, and environmental exposures. Our findings suggest that higher outdoor LAN levels are associated with larger BMI Z-scores and greater odds of overweight (including obesity) and obesity in school-aged children and adolescents. Further, the association between outdoor LAN levels and BMI Z-scores is stronger in males. Future studies with exposure assessments that consider both outdoor and indoor LAN exposures are needed. Graphical abstract: Image 1 Highlights: We studied 47, 990 Chinese children in a cross-sectional study. Outdoor light at night was positively related to BMI Z-score. Outdoor light at night was positively related to the risk of overweight/obesity. The association of outdoor light at night with BMI Z-score was stronger in males.